Successful high dose antipsychotic treatment with cariprazine in patients on the schizophrenia spectrum: Real-world evidence from a Spanish hospital setting - Galmes, Lluis Niell; Rancans, Elmars (Frontiers in Psychiatry, 2023)
Real-world evidence fills in an important gap by providing data on the effectiveness and tolerability of new medications in everyday patients. In this data collection form a Spanish hospital, the effectiveness and tolerability of cariprazine were evaluated in 14 patients who were admitted to the hospital due to an acute episode of schizophrenia or schizoaffective disorder. The collected data included demographic characteristics, history of disorder and previous treatment, and details of cariprazine therapy such as dosing, side effects and measurements of effectiveness via scales. Difference between admission and discharge on the Brief Psychiatric Rating Scale (BPRS) and Clinical Global Impression – Severity (CGI-S) scale scores were evaluated using the Wilcoxon Signed-Rank test. Significant improvement was detected in nearly all patients (one patient dropped out) as measured by the BPRS Total, Negative symptom, Positive symptom, and Hostility scores. At admission, patients were markedly-moderately ill and at discharge the severity was reduced to borderline ill and normal according to the CGI-S. The CGI-Improvement scale also indicated very much and much improvement at discharge. Importantly, patients left the hospital with high doses of cariprazine i.e., 7.5 mg/day or even 9.0 mg/day, but this did not cause safety problems; cariprazine well-tolerated as only a few patients experienced side effects such as akathisia. The results provide novel evidence regarding the tolerability and effectiveness of cariprazine in high doses patients on the schizophrenia spectrum.